Community acquired Acinetobacter baumannii in pediatric patients under 1 year old with a clinical diagnosis of whooping cough in Lima, Peru - Peña-Tuesta, Isaac (2021)
Objective: This study aimed to determine the prevalence of A. baumannii in children aged less than 1 year admitted with a clinical diagnosis of whooping cough. Results: A total of 225 nasopharyngeal samples from children under 1 year old hospitalized with clinical diagnosis of whooping cough were studied from January 2010 to July 2012. The presence of A. baumannii was detected in 20.89% (47/225) of the nasopharyngeal swab samples. Among the 47 patients with A. baumannii: 5 were diagnosed with A. baumannii monoinfection, 17 co-infection with bacteria, 7 co-infection with virus and 18 co-infection with bacteria + virus. It was observed that 51.6% (116/225) were children between 29 days and 3 months old, this same group had the highest overall prevalence with 53.3%. The most common co-infecting pathogens were Bordetella pertussis in 55.3%, Adenovirus in 42.6% and Mycoplasma pneumoniae in 23.4%.